Prevalence of Ten Gene Variants Involved in Muscular Phenotypes in a Mexican Mestizo Population - Luz Berenice López-Hernández; Guillermina Avila-Ramírez; Ariadna Del Villar-Morales; Mónica Alejandra Anaya-Segura; Luis Angel Montes-Almanza; Froylan Arturo García-Martínez; Antonio Miranda-Duarte; Carlos Antonio Sosa-Flores; Martha Eunice Rodríguez-Arellano; Ileana Chavez-Maisterra; Alexandra Berenice Luna-Angulo; Miriam Pavelth Casillas-Ávila; et al. (Muscles, 2023)
Several reports have provided evidence that there are genetic variants of genes such as MSTN, BDRKB2, ACTN3 and ADRB2 that are involved in a better response to adaptation during resistance or strength training, while other genes such as GRB14, AGT and END1 are reported to be associated with the risk of suffering from some diseases such as diabetes, hypertension or obesity. A cross-sectional study from a Mexican Mestizo population was performed to estimate the frequency of 10 gene variants in 8 genes involved in athletic performance or chronic degenerative diseases, MSTN (rs1805085, rs1805086), BDKRB2 (rs1799722), FST (rs1423560), ACTN3 (rs1815739), ADRB2 (rs1042713, rs1042714), GRB14 (rs8192673), AGT (rs699) and EDN1 (rs5370), and to compare frequencies from 26 populations reported in the Database of 1000 Genomes project. Genotype frequencies fitted the Hardy–Weinberg equilibrium, except for MST rs1805086 and FST rs1423560, and our study revealed significant differences in the distribution of frequencies of some of these gene variants among populations reported in the 1000 Genomes Project. Our findings provide insights regarding the genetic background of our population, and future case–control studies can be carried out with more accurate sample sizes for genetic association studies. Our results may be also useful in recognizing the roles and mechanisms contributing to athletic performance and/or chronic degenerative diseases in Mexicans.